3,4,5-Trihydroxy-N′-(1H-indol-2-ylmethylidene)benzohydrazide–1H-indole-2-carbaldehyde azine–methanol (2/1/2) - Hamid Khaledi; Abeer A. Alhadi; Hapipah Mohd Ali; Ward T. Robinson; Mahmood A. Abdulla (Acta Crystallographica Section E, 2010)
The title compound, 2C16H13N3O4·C18H14N4·2CH4O, was crystallized from the reaction between 3,4,5-trihydroxybenzoylhydrazine and indole-2-carbaldehyde in a mixture of ethanol and methanol. The compound is a stoichiometric 2:1 cocrystal of the methanol-solvated reaction product, 3,4,5-trihydroxy-N′-(1H-indol-2-ylmethylidene)benzohydrazide and 1H-indole-2-carbaldehyde azine that arose unexpectedly during the synthesis. The former molecules are linked by O—H...O hydrogen bonds and also by π–π stacking interactions between benzoylhydrazide rings into a two-dimensional network. The methanol solvent molecules are hydrogen bonded to this network. The centrosymmetric azine molecules are not engaged in hydrogen bonding.